Construction of a Plasmonic Chip for Metabolic Analysis in Cervical Cancer Screening and Evaluation. Issue 4 (25th August 2019) - Shu, Weikang; Wang, You; Liu, Chao; Li, Rongxin; Pei, Congcong; Lou, Weihua; Lin, Sihan; Di, Wen; Wan, Jingjing
Abstract: There is a high demand for high‐throughput in vitro metabolic analysis in clinical practice. However, current metabolic analysis of biofluids requires tedious sample pretreatment due to sample complexity and low molecular abundance. Herein, a plasmonic chip with Au nanoparticles deposited on a dopamine‐bubble layer is constructed for clinical metabolic fingerprints. The structural parameters of the designed chip are optimized in terms of surface roughness and Au content. The established chip enables fast, sensitive, and selective detection of small metabolites in human serum without any enrichment or purification. On‐chip serum fingerprints further allow for differentiation between women diagnosed with cervical cancer and control subjects, as well as the therapeutic evaluation for potential clinical monitoring. This work boosts the application of laser desorption/ionization mass spectrometry in large‐scale clinical in vitro diagnosis. Abstract : A robust analytical platform based on a plasmonic gold chip for metabolic fingerprinting of biofluids in diagnostics is established in this work. High‐throughput and micro/nanoscaled sample analysis can be realized when coupling with microarrays printing. Moreover, on‐chip in vitro cancer screening and therapeutic evaluation for cervical cancer is demonstrated for the first time.